PENGARUH KEDISIPLINAN TERHADAP KEPUASAN KERJA PEGAWAI (STUDI PEGAWAI POLITEKNIK ILMU PELAYARAN SEMARANG) - Janny Adriani Djari; Firdaus Sitepu (Dinamika Bahari, 2017)
The purpose of this study to examine the effect discipline by job satisfaction of employees in Seamanship Polytechnic Semarang. Under these conditions, this study took the title "The Effect of Discipline Against by Employee Job Satisfaction (Study of Employee Seamanship Polytechnic Semarang)" . In this study took the population in this study were employees of the Polytechnic Semarang Seamanship, amounting to 218 persons. Sampling with random sampling technique that randomly sampling 142 respondents. Based on the research that has been done it is known discipline effect on job satisfaction.